2015
DOI: 10.1093/jmammal/gyu005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of invasive feral cats on San Clemente Island: implications for control and management

Abstract: Feral cats, Felis catus, inhabiting San Clemente Island, California, are both predators and competitors of multiple sympatric endemic species. To improve our understanding and management of these invasive predators, we used GPS-equipped radiocollars to track 11 (6F:5M) cats for a total of 3,108 days, resulting in 15,419 GPS locations. Average 100% minimum convex polygon, 95% kernel density, and 50% kernel density estimates were 229, 132, and 33 ha, respectively. The point estimate for average male home-range s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Roads may accelerate the spread of invasive vertebrate predators by allowing species to move efficiently across landscapes and colonize areas that they would otherwise take longer to reach (Hradsky et al, 2017; Raiter et al, 2018). Studies in Australia have generally found feral cats preferentially travel along linear features like roads but see Bridges et al (2015) (Wang & Fisher, 2012; Wysong, Hradsky, et al, 2020; Wysong, Iacona, et al, 2020). Within the AWT there is an extensive network of roads bisecting otherwise intact habitats, and feral cats may have been using them undetected for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Roads may accelerate the spread of invasive vertebrate predators by allowing species to move efficiently across landscapes and colonize areas that they would otherwise take longer to reach (Hradsky et al, 2017; Raiter et al, 2018). Studies in Australia have generally found feral cats preferentially travel along linear features like roads but see Bridges et al (2015) (Wang & Fisher, 2012; Wysong, Hradsky, et al, 2020; Wysong, Iacona, et al, 2020). Within the AWT there is an extensive network of roads bisecting otherwise intact habitats, and feral cats may have been using them undetected for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Roads may accelerate the spread of invasive vertebrate predators by allowing species to move efficiently across landscapes and colonize areas that they would otherwise take longer to reach (Hradsky et al, 2017;Raiter et al, 2018). Studies in Australia have generally found feral cats preferentially travel along linear features like roads but see Bridges et al (2015) (Wang & Fisher, 2012;Wysong, Hradsky, et al, 2020;. Within the AWT there is an extensive network of roads bisecting otherwise intact habitats, and feral cats may have been using them undetected for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Roads may accelerate the spread of invasive vertebrate predators by allowing species to move efficiently across landscapes and colonize areas that they would otherwise take longer to reach (Hradsky et al, 2017;Raiter et al, 2018). Studies in Australia have generally found feral cats preferentially travel along linear features like roads but see Bridges et al (2015) (Wang & Fisher, 2012;Wysong, Hradsky, et al, 2020;. Within the AWT there is an extensive network of roads bisecting otherwise intact habitats, and feral cats may have been using them undetected for decades.…”
Section: Introductionmentioning
confidence: 99%